2003
DOI: 10.14295/rbho.v9i1.161
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização física e conservação pós-colheita de alpínia.

Abstract: O mercado de flores tropicais está em franca expansão. Nele é crescente a comercialização de alpínias como flores de corte. Considerando-se que, no Brasil, os estudos sobre pós-colheita de flores tropicais são escassos, o objetivo deste trabalho foi desenvolver métodos de manuseio e conservação de inflorescências de alpínia (<i>Alpinia purpurata Vieill. Schum</i>.) por longos períodos, uma vez que essa espécie tropical começa a ser introduzidas no mercado sem nenhum conhecimento prévio de pós-colhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…To this end, 10 freshly cut flower stems were placed in buckets with 5 L water and, every two days, the water was exchanged. This evaluation was based on a 1 -4 grade scale, adapted from Dias-Tagliacozzo et al (2003). The evaluation was always carried out by the same evaluator, who assigned: grade 4 to inflorescences with an excellent general appearance, bright turgid bracts and green leaves; grade 3 to good general appearance, beginning gloss loss of bracts, onset of leaf yellowing; grade 2 for poor overall appearance, with yellow and dry leaves, gloss loss of the bracts and inclining of the inflorescence; grade 1 for disposal ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, 10 freshly cut flower stems were placed in buckets with 5 L water and, every two days, the water was exchanged. This evaluation was based on a 1 -4 grade scale, adapted from Dias-Tagliacozzo et al (2003). The evaluation was always carried out by the same evaluator, who assigned: grade 4 to inflorescences with an excellent general appearance, bright turgid bracts and green leaves; grade 3 to good general appearance, beginning gloss loss of bracts, onset of leaf yellowing; grade 2 for poor overall appearance, with yellow and dry leaves, gloss loss of the bracts and inclining of the inflorescence; grade 1 for disposal ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The initial and postharvest development of Alpinia sp. was studied in Lavras, Minas Gerais (Dias-Tagliacozzo et al, 2003); cultivation and commercialization of Alpinia in the state of Pernambuco (Teixeira and Loges, 2008); seedling production of Alpinia purpurata (Vieill. ), cultivar "Red Ginger", with different substrates and a rooting stimulator in Aracaju, Sergipe (Moreira et al, 2011); and the pollen viability of Alpinia zerumbet by colorimetric tests in the state of Mato Grossso (Macedo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another phytohormone used is cytokinin. Dias-Tagliacozzo et al (2003) studied red ginger flowers, and found that cytokine (200 ppm), associated to sucrose, increased the longevity of flower stalks, when compared to the treatment in which cytokinin was used alone, indicating that different substances must be tested together.…”
Section: Physiological Factors In Postharvestmentioning
confidence: 99%
“…A qualidade e o tempo de vida pós-colheita de flores estocadas ou transportadas em temperaturas amenas podem ser aumentados tratando-as com condicionamentos específicos ou soluções de absorção rápida (solução de fortificação), imediatamente antes e ou após a estocagem ou o transporte (HALEVY & MAYAK, 1981). Os grupos de componentes comumente usados em soluções conservantes são os carboidratos, os germicidas e os inibidores da produção ou da ação do etileno (íons de prata e outros) (DIAS-TAGLIACOZZO et al, 2003). Os reguladores vegetais, principalmente giberelina e citocinina, merecem destaque, pois podem interferir na senescência de folhas (FRANCO & HAN, 1997 (JACOMINE et al, 1976).…”
Section: Maria Herbênia Lima Cruzunclassified
“…Esses resultados estão de acordo com os resultados de PAULL & CHANTRACHIT (2001) e DIAS- TAGLIACOZZO & CASTRO (2005).…”
Section: Maria Herbênia Lima Cruzunclassified